COMPARATIVE ANALYSIS BETWEEN THE DESTRUCTIVE BENDING MOMENTS OF END AND T-SHAPE CORNER JOINTS OF DETAILS FROM SOLID CHESTNUT WOOD WITH TWO TYPES OF CROSS SECTION (Innovation in Woodworking Industry and Engineering design, 2026)
A comparative analysis has been done on the experimentally found destructive bending moments in the loading of bending of the most commonly used end and T – shape corner joints of details from solid chestnut wood with two types of cross section of the details – 50 x 25mm and 50 x 30mm.It has been found, that the type of joints and the thickness of the joining details have a definite impact on their destructive bending moments.With the increase of the thickness of the details from 25 to 30 mm (with 20 %), the destructive bending moments in the loading of bending of the end glued and dismountable corner joints increase respectively with around 28 % and with 33 %, and of the T – shape corner joints – with around 23 % and around 17 %.It is recommended that the found out destructive bending moments in the loading of bending and the most commonly used end and T – shape corner joints of details from solid chestnut timber with cross section 50 x 25mm and 50 x 30 mm be taken into consideration in the choice of the type of joints in the sitting furniture construction.